Teologi Politik Berbalu SARA Antara Ambisi dan Konspirasi - Ritau'din, M. Sidi (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
In a multi-cultural democracy based on Pancasila philosophy of independence, ethnic, religious, racial and intergroup issues it call (SARA) are political indicators that can trigger conflict and division. If the player is ambitious and power-hungry, then he will not hesitate to do everything he can to gain power, even build a big conspiracy using SARA as a tool to divide the ummah, then he emerges as a unifier and presents programs prestigious sympathetic, there Imaging actions and slogans of the pro poor people, but essentially no more as political deceit, a false gift of hope, it familiar said (PHP) that never realized, only reap the political advantage in the game of SARA, even not hesitate to shout thief when he Itself is a thieving thief based on greed and greed where the horizontal relations of fellow human beings deny the bond of faith as the foundation. Political conspiracy based on political interests and abuse of power, an action of political pathology that is not civilized that has become a trend of contemporary politics and globalization.